Review on the dynamics of semiconductor nanowire lasers - Roeder, Robert; Ronning, Carsten (Semiconductor Science and Technology, 2018)
Semiconductor optoelectronic devices have contributed tremendously to the technological progress in the past 50-60 years. Today, they also play a key role in nanophotonics stimulated by the inherent limitations of electronic integrated circuits and the growing demand for faster communications on chip. In particular, the field of 'nanowire photonics' has emerged including the search for coherent light sources with a nano-scaled footprint. The past decade has been dedicated to find suitable semiconductor nanowire (NW) materials for such nanolasers. Nowadays, such NW lasers consistently work at room temperature covering a huge spectral range from the ultraviolet down to the mid-infrared depending on the band gap of the NW material. Furthermore, first approaches towards the modification and optimization of such NW laser devices have been demonstrated. The underlying dynamics of the electronic and photonic NW systems have also been studied very recently, as they need to be understood in order to push the technological relevance of nano-scaled coherent light sources. Therefore, this review will first present novel measurement approaches in order to study the ultrafast temporal and optical mode dynamics of individual NW laser devices. Furthermore, these fundamental new insights are reviewed and deeply discussed towards the efficient control and adjustment of the dynamics in semiconductor NW lasers.
CRIS-Team Scopus Importer:2023-04-20
Keywords: laser onset; lasing; nanowire; optical mode; pulse width; semiconductor; ultrafast emission